Contexto da experiência em um ecossistema de serviço - Gauze, Ioná Plein Bolzan (2016)
This study aimed to analyze the context of the experience in a service ecosystem, trying to understand how the different actors contribute and relate to an event can happen. Studies indicate the need for empirical research based on different contexts in service ecosystems. Therefore, this study aimed to investigate the context of the experience of a service ecosystem in a specific event, the wedding. For the goal was reached, we used the case study as a research strategy. Data were collected from diaries, interviews and participant observation. The participants were the bride and groom and two suppliers contracted for the event. We used the content analysis technique to analyze the data, with the aid of NVivo software. The following categories were established: a) social structures and institutions; b) the context of co-creation experience; c) role of symbols in the co-creation of value and d) value in social context. The results point to the importance of interaction between the different actors to cocreation can happen, since it does not occur in isolation and is generated for and with all stakeholders of an event. Also, during the exchange meeting, the presence of guests and the network providers have brought about social interactions and perceptions of value.